Evaluation method for hydrogen-induced cracking resistance of steel
Patent Information
- Application Number
- JP2021153960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-22
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2041-09-22
AI Technical Summary
【0016】 本発明を適用することで、溶鋼の成分分析と鋳片での偏析調査が完了した段階で耐水素誘起割れ性に優れた鋼かどうかを評価できる。この結果をもとに鋳片以降の鋼材の用途を決めることができることから、HIC特性を要求されない用途に適用した鋼材にはHIC試験は不要となるため、HIC試験に要する工程の短縮が可能である。また、偏析状況に応じて、加熱、均熱処理により偏析を拡散させる対応も可能となり、成品歩留りを向上させることが可能である。
Smart Images

Figure 0007636672000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for evaluating the hydrogen-induced cracking resistance of a steel material, and relates to an evaluation method for a steel material for determining whether or not the steel has excellent hydrogen-induced cracking resistance when manufacturing hydrogen-induced cracking resistant steel intended for use in line pipes. [Background technology]
[0002] It is known that in continuous cast steel slabs (hereinafter simply referred to as slabs), segregation at the center of the slab (hereinafter referred to as center segregation) has a significant effect on the properties of the steel material. In particular, sour-resistant steels used as line pipes are expected to be used in hydrogen sulfide environments, and depending on the state of center segregation and nonmetallic inclusions, hydrogen induced cracking (hereinafter referred to as HIC) may occur starting from them. In order to suppress HIC, it is effective to suppress the formation of manganese sulfide (MnS), a highly ductile sulfide-based inclusion, and measures have been taken such as reducing the S concentration in molten steel to the minimum and adding Ca to molten steel to control the shape to non-ductile calcium sulfide (CaS). In addition, the aggregates of segregated elements such as Mn in the center segregation area have a different hardness from the surrounding base material, and these also become the starting point of HIC, so measures have been taken to suppress factors that worsen center segregation, such as adjusting the roll gap during casting and not changing the casting speed. However, even if these measures are taken, inclusions and center segregation may occur due to compositional variations and casting conditions. Therefore, the HIC properties of steel materials are evaluated before product shipment.
[0003] [Method of evaluating HIC characteristics] When evaluating the HIC properties of steel, the steel is often subjected to the HIC test (NACE test) specified in the standard TM0284 of the National Association of Corrosion Engineers (NACE) before shipping. This method involves immersing a steel of a specified size in a mixed solution of 5% NaCl solution saturated with 1 atm hydrogen sulfide and 0.5% acetic acid at pH 2.7, and then removing it after 96 hours to evaluate the occurrence of HIC. Methods for evaluating the occurrence of HIC include observing the cross section of the steel to investigate the crack length and shape of the HIC that has occurred inside, and using ultrasonic testing (UT) to calculate the crack area ratio (CAR) of the crack area on the evaluation surface of the test piece.
[0004] By applying the above method to products before shipment, it is possible to check for the occurrence of HIC, but this method takes several weeks until the results become clear. If HIC occurs, the product cannot be used as a sour-resistant material, and if it has to be remelted, production efficiency will decrease significantly. Therefore, the following method has been disclosed as a method for estimating the occurrence of HIC at the slab stage instead of the NACE test, which takes several weeks until the results become clear.
[0005] Patent Document 1 discloses a method for redirecting a sour steel slab based on quality assessment using the opening thickness of horizontal cracks in a range of width D / 2 from both ends in the width direction on the cut surface of the slab, the maximum segregation grain size in a range of width WD excluding D / 2 from both ends in the width direction, and the number density of segregation grains of a predetermined diameter or more.
[0006] In Patent Document 2, the major diameter D obtained by approximating the Mn segregation spot of the central segregation part to an ellipse L and Mn segregation degree C MnS / C 0 This paper discloses a method for evaluating the HIC susceptibility of steel materials, in which a steel material is evaluated as having excellent HIC resistance when the number of Mn segregation spots where the product of x and y exceeds 0.8 mm is 1 or less per 100 mm.
[0007] In Patent Document 3, a 20 mm thick mirror-polished surface of calcium-added steel is 2The above was observed with an SEM, and the composition of nonmetallic inclusions was analyzed with EDS to determine CaO and Al. 2 O 3 Concentration ratio (mass% CaO / mass% Al 2 O 3 A method is disclosed in which the hydrogen-induced cracking resistance of calcium-added steel is estimated by counting the number of nonmetallic inclusions with a coefficient of thermal expansion (SST) in the range of 1.0 to 10.0 and using a relational equation with the hydrogen-induced cracking resistance property. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2014-172074 A [Patent Document 2] JP 2014-77642 A [Patent Document 3] JP 2015-59880 A Summary of the Invention [Problem to be solved by the invention]
[0009] Patent Documents 1 and 2 are methods for evaluating HIC properties from the size or number density of segregation grains. Patent Document 3 is a method for evaluating HIC properties from nonmetallic inclusions. Many of the prior art HIC property evaluation methods focus on either segregation or inclusions, and do not address the combined causes of segregation and inclusions. It is believed that the threshold value for determining HIC properties is set on the safer side than in reality.
[0010] In view of the above, an object of the present invention is to provide a method for evaluating the hydrogen-induced cracking resistance of a steel material at the slab stage with higher accuracy than conventional methods. [Means for solving the problem]
[0011] The inventors of the present invention considered that the inclusions that collect hydrogen in steel exist at the initiation point of hydrogen-induced cracking, and that MnS has a large influence among them. MnS is generated at the stage of solidification of molten steel depending on the Mn and S concentrations in the steel. Since Mn is at a sufficiently high concentration compared to S in molten steel, the amount of MnS generated generally depends on the S concentration. When Ca is present in molten steel, CaS is formed at the molten steel stage, so if the S concentration excluding this CaS (=free S) is known, the amount of MnS generated at the solidification stage can be roughly determined. At this time, Mn and S are concentrated in the segregation part, but the effect of MnS itself reflects the MnS generation state of the base material, and it was considered that the frequency of it becoming the initiation point of cracking can be examined by focusing on free S.
[0012] They also considered that the degree of hydrogen-induced cracking is greatly affected by the distribution of segregation grains, which have a different hardness from the base material. They also considered that when focusing on a single segregation grain, the larger the size of the segregation grain, the stronger its susceptibility to cracking. Furthermore, they considered that when multiple segregation grains are adjacent to each other, if the distance between the segregation grains is short, a chain reaction of cracks will occur.
[0013] Therefore, the inventors investigated the correlation between the molten steel components in the tundish and the central segregation of the slab, and the CAR, which is an evaluation index of the occurrence of HIC in the product. The CAR is the area ratio of the cracked part to the evaluation surface of the test piece, and is suitable for quantitatively grasping the occurrence of HIC. As a result, it was found that the CAR correlates with the MnS generation state estimated from the molten steel components and the size of the segregated grains in the central segregation part. In addition, it was also found that HIC does not occur under conditions where MnS is not generated, even if the distribution state of the segregated grains is the same in the central segregation zone. Considering the HIC occurrence mechanism in which cracks occur due to the internal pressure of H gathered around MnS, etc., in a situation where MnS is not generated, there is no trigger for HIC to occur, so it is considered that HIC does not occur regardless of the degree of segregation, and the CAR is 0. In addition, the correlation between the CAR and the size of the segregated grains is considered to be due to the fact that the critical stress at which one segregated grain leads to cracking differs depending on the size of the segregated grains, and even under conditions where MnS is distributed at the same density, the larger the segregated grain, the smaller the critical stress at which cracking occurs.
[0014] Furthermore, it was found that the CAR correlates with the distribution of segregation grains. Even if HIC occurs, if the segregation grains are separated, the cracks will not propagate and the CAR will be low. However, if the segregation grains are continuously distributed, the internal pressure of H will affect the adjacent segregation grains through the matrix, causing large-scale cracks and resulting in a high CAR.
[0015] Considering the influence of the MnS formation state, the size of the segregated grains, and the distribution state of the segregated grains on the occurrence of HIC described above, specific means for solving the problems are as follows: [1] A method for evaluating the resistance of steel to hydrogen-induced cracking, characterized in that the resistance is evaluated based on the free S concentration calculated from the component analysis values of a molten steel sample taken from a tundish and the evaluation results of the segregation grains in the central segregation zone appearing in a cross section perpendicular to the longitudinal direction of the cast slab. [2] The method for evaluating hydrogen-induced cracking resistance of a steel material according to [1], characterized in that the steel material is evaluated as having excellent hydrogen-induced cracking resistance when, among the segregation grains on a straight line (segregation line) of a predetermined investigation length drawn in the width direction of the slab so as to overlap the most segregation grains in the central segregation zone, the total length of segregation grains (target segregation grains) having a length (the length of a portion where the segregation grains and the segregation line overlap) of 1.0 mm or more is less than 45% of the investigation length and / or the maximum length of the target segregation grains is less than 3.0 mm, and the free S concentration is 20 ppm by mass or less. [3] The method for evaluating hydrogen-induced cracking resistance of a steel material according to [1] or [2], characterized in that the steel material is evaluated as having excellent hydrogen-induced cracking resistance when, among the segregation grains on a straight line (segregation line) of a predetermined investigation length drawn in the width direction of the slab so as to overlap the most segregation grains in the central segregation zone, the total length of segregation grains (target segregation grains) having a length (the length of a portion where the segregation grains and the segregation line overlap) of 1.0 mm or more is 45% or more of the investigation length, and the maximum length of the target segregation grains is 3.0 mm or more, and the free S concentration is 6 ppm by mass or less. [4] E for each variety in advance CaOThe method for evaluating hydrogen-induced cracking resistance of steel material according to [2] or [3], characterized in that the free S concentration (the proportion (mol %) of CaO in all oxides in the molten steel) is obtained in advance, and the free S concentration is calculated based on the component analysis values of the sample in accordance with the following formulas (1) to (3). Ca CaO =(TO / 16)·40.078·(E CaO / 100) ···(1) S CaS =(Ca-Ca CaO )·32 / 40.078 ···(2) Free S=SS CaS (3) TO is the total oxygen concentration analysis value (ppm by mass), Ca is the Ca concentration analysis value (ppm by mass), and S is the S concentration analysis value (ppm by mass). Effect of the Invention
[0016] By applying this invention, it is possible to evaluate whether a steel has excellent resistance to hydrogen-induced cracking after the composition analysis of molten steel and the segregation investigation of the cast slab are completed. Based on this result, the use of the steel after the casting can be decided, so that the HIC test is not necessary for steel used for the application that does not require HIC properties, and it is possible to shorten the process required for the HIC test. In addition, it is possible to diffuse the segregation by heating and soaking treatment depending on the segregation state, which makes it possible to improve the product yield. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, preferred embodiments of the present invention will be described. 1. Definitions of Terms Used in the Invention A tundish is a holding vessel that temporarily holds molten steel from a ladle until it is poured into a mold. In many cases, molten steel samples taken in a tundish are used as representative components of the steel product, and in this invention, the HIC resistance of the steel product is evaluated using the analysis results of the molten steel samples taken in the tundish.
[0018] Free S refers to the S in the sample taken from the tundish at the molten steel stage, excluding the S fixed as CaS, that becomes dissolved S and MnS in the cast slab. Because it is affected by the molten steel composition, it can be estimated using the formula described below.
[0019] Segregation is a bias in steel components caused by the obstruction of flow between dendrites that occurs when molten steel solidifies, and central segregation occurs in the thickness center of a cast slab. The ease of segregation varies depending on the steel components, and Mn, P, and S are elements that are prone to segregation. Segregation can be evaluated using the etch print method or EPMA (Electron Probe Micro Analyzer) method. The etch print method involves corroding the surface of a sample using an etching solution mainly composed of picric acid, cleaning and drying the sample, infiltrating polishing powder into the corrosion pits on the corroded polished surface, attaching transparent adhesive tape to the polished surface, adhering the polishing powder in the corrosion pits to the transparent adhesive tape, peeling off the adhesive tape, attaching it to a white mount, and evaluating the segregation by its shade. The EPMA method involves irradiating the polished surface with an electron beam to obtain a concentration map of Mn, etc., and evaluating the segregation by the concentration difference with the matrix. In addition to EPMA, analytical methods such as CMA (Computer aided Micro Analyzer) and MA (Macro Analyzer) can also be used. The C-section refers to a surface perpendicular to the longitudinal direction (casting direction) of the slab.
[0020] 2. Processing Procedure A specific processing procedure using the present invention is shown below.
[0021] The molten steel produced in a steelmaking furnace such as a converter or electric furnace is adjusted in composition as necessary using a ladle refining device such as an LF or a degassing device such as an RH or REDA, and then cast pieces are produced in a continuous casting machine. The analytical values of the molten steel sample taken in the tundish can be used as representative values for the molten charge. Free S is calculated using the S, O, and Ca concentrations from the analytical values according to the calculation method described below.
[0022] The centerline segregation is evaluated by cutting a part of the produced slab and examining the C-section of the slab. As a method for evaluating centerline segregation, the etch print method or an EPMA can be applied, as described later. This evaluation makes it possible to calculate the length and number of segregated grains in the centerline segregation area.
[0023] Once the length and number of the segregated grains in the free S and central segregation area are determined, the hydrogen-induced cracking resistance is determined according to the method described in the claims. Cast pieces that are judged to have good hydrogen-induced cracking resistance can proceed directly to the next process, while cast pieces that are judged to be poor can be treated by lowering the product grade, changing the destination, or sending them to a process to diffuse the segregation through processing, heat treatment, etc.
[0024] 3. Calculation method for free S In molten steel samples taken from the tundish, most of the O is in the form of oxides, and a small amount is dissolved in the molten steel as dissolved O, but at the solidification stage, almost all of it forms oxides. Ca also forms CaO or CaS. Meanwhile, at the molten steel stage, S exists as dissolved S other than CaS, and at the solidification stage, dissolved S combines with Mn to form MnS. Therefore, if the proportion of oxides in O, particularly the amount present as CaO, is known, the free S concentration can be calculated using equations (1) to (3).
[0025] First, the CaO concentration forming CaO in molten steel is calculated using equation (1). Ca CaO =(TO / 16)·40.078·(E CaO / 100) ···(1) Here, Ca CaO is the Ca concentration forming CaO (ppm by mass), TO is the total oxygen concentration analysis value (ppm by mass), E CaO is the ratio (mol%) of CaO to all oxides in the molten steel, 16 is the atomic weight of O, and 40.078 is the atomic weight of Ca.
[0026] Next, the S concentration (ppm by mass) forming CaS is calculated using equation (2). S CaS=(Ca-Ca CaO )·32 / 40.078 ···(2) Here, S CaS is the S concentration (ppm by mass) forming CaS, Ca is the Ca concentration analysis value (ppm by mass), and 32 is the atomic weight of S.
[0027] The S concentration S forming CaS calculated from the S concentration analysis value S (mass ppm) of molten steel using formula (2) is CaS Free S can be calculated by subtracting (ppm by mass). Free S=SS CaS (3)
[0028] In addition, in the formula (2), (Ca-Ca CaO )<0, then S CaS is set to 0, and SS in equation (3) CaS If <0, free S is set to 0.
[0029] Equation (1) CaO The composition of oxides is analyzed using an energy dispersive X-ray analyzer (EDS) attached to a scanning electron microscope (SEM), and the results are converted into oxides to be used for evaluation as the ratio (mol%) of CaO to all oxides. Oxides vary in size and composition, but the product of the area of the oxides investigated and the concentration of each component is integrated, and the integrated CaO value is divided by the total integrated total of all oxide species to determine the ratio of CaO to all oxides. In order to increase representativeness, it is desirable to investigate 100 or more oxides. When the inventors investigated molten steel samples taken from a tundish, the oxide composition ratio was roughly the same for the same steel type. Therefore, the ratio E of CaO to all oxides in molten steel is calculated by multiplying the area of the oxides investigated by the product of the concentration of each component and the integrated CaO value by the total integrated total of all oxide species. CaO The (mol%) should be determined in advance for each steel type, and the calculated value should be used to calculate formula (1).
[0030] 4. Evaluation method for segregated parts of cast slabs A plane (C-section) perpendicular to the longitudinal direction (casting direction) is cut out from the slab, and the segregation areas seen on the C-section are evaluated using techniques such as etch printing and EPMA. In the case of slabs, the segregation areas are usually present in the center of the slab (1 / 2 the thickness in the thickness direction, and 1 / 2 the thickness or more from the left and right ends in the width direction).
[0031] When applying the etch print method, the entire width of the slab may be measured, but the results of a partial investigation may also be used. A grayscale image of an etch print with a region including a segregation part transferred thereto is photographed, and the image converted to grayscale is binarized. The binarized thickened part is regarded as a segregation part, and one lump of the segregation part is called a segregation grain. The threshold value for binarization may be set to the middle of the pixel average of the base material part (the bright part away from the segregation part) and the pixel average of the segregation part (the part that looks darker than the surroundings due to the accumulation of iron powder). A straight line of a predetermined investigation length is drawn in the width direction of the slab so as to overlap the segregation grain most on the image in the central segregation zone, and the segregation line is set. The length of the segregation grains present on the straight line (segregation line) (the length of the part where the segregation grain and the segregation line overlap) is evaluated. Then, the ratio of the total length of the segregation grains (target segregation grains) with the length of 1.0 mm or more to the investigation length is calculated. In addition, the maximum length of the target segregation grains is evaluated.
[0032] In the EPMA method, a test piece containing segregated areas can be cut out and a mapping image of the solute elements can be obtained. The target element is generally Mn, and the Mn concentration in the base material is Mn and the Mn concentration in the EPMA measurement area is Mn. Seg Regarding the relationship with Mn Seg The parts where / Mn=1.3 or more can be treated as segregated parts. As with the etch print method, a straight line (segregation line) is drawn in the width direction of the slab on the obtained element mapping image, and the length of the segregated grains on that line, the ratio of the segregated grains to the surveyed length (total length of segregated grains / surveyed length), and the maximum length can be calculated.
[0033] In the present invention, it is desirable to investigate the segregation part for an investigation length of at least 25 mm or more, and investigation lengths can be added or multiple locations can be investigated as necessary. When investigating partially, the investigation position in the width direction can be between 1 / 2 width and 1 / 4 width to ensure representativeness. In the present invention, when the total length of the segregation grains (target segregation grains) with a length of 1 mm or more among the segregation grains present on the segregation line of the investigation length is 45% or more of the investigation length and the maximum length of the target segregation grains is 3.0 mm or more, the investigation evaluation of the segregation part of the investigated slab is A, and when the total length of the target segregation grains with a length of 1 mm or more is less than 45% of the investigation length and / or the maximum length of the target segregation grains is less than 3.0 mm, the investigation evaluation is B. In the present invention, when quantitatively evaluating the dispersion state of the segregation grains, the segregation grains with a length of 1 mm or more are evaluated, because it is considered that the cracks associated with HIC do not easily progress in the segregation grains with a length of less than 1 mm, the investigation evaluation is performed on the segregation grains with a length of 1 mm or more. The etch print method and the method using EPMA are evaluation methods based on the difference in concentration of solute elements between the base material and the segregation portion, and either method may be used to evaluate the segregation portion.
[0034] Based on the grading evaluation results of the slab segregation parts obtained as described above and the results of free S calculated from the component values of the slab, the steel material was judged as to whether it had excellent resistance to hydrogen-induced cracking as follows.
[0035] 5. Method for determining HIC characteristics In the present invention, the influence of the evaluation results of free S and segregation calculated by the above-mentioned method on HIC characteristics was examined, and a method for judging HIC characteristics based on the evaluation results of free S and segregation was established based on the results. In this embodiment, the HIC characteristics are evaluated by CAR, and the relationship between free S and segregation and CAR is obtained in advance, and the conditions of free S and segregation that obtain good HIC characteristics are set. First, a NACE test was performed on a rolled steel sheet. That is, the steel sheet was immersed in a mixed aqueous solution of 5% NaCl solution saturated with 1 atm hydrogen sulfide and 0.5% acetic acid at pH 2.7, and taken out after 96 hours. Next, as a method for evaluating the occurrence of HIC, ultrasonic flaw detection (UT) was used to calculate the area ratio CAR of cracks on the evaluation surface of the test piece.
[0036] In this embodiment, when the CAR was less than 5.0%, the HIC characteristics were judged to be good. Next, the relationship between the ratio of the total length of the segregated grains, the maximum length, and the free S conditions evaluated above and the conditions for a CAR of less than 5.0% was evaluated. As a result, as described in detail in the examples below, it was found that when the total length of the segregated grains of 1.0 mm or more on the segregation line is less than 45% of the investigated length and / or the maximum length of the segregated grains is less than 3.0 mm (evaluation B) and the free S concentration calculated based on the component analysis value of the sample taken in the tundish is 20 mass ppm or less, the HIC characteristics are excellent (CAR is less than 5.0%). In addition, it was found that when the total length of segregated grains of 1.0 mm or more on the segregation line is 45% or more of the investigated length and the maximum length of the segregated grains is 3.0 mm or more (evaluation A described above), the HIC characteristics are excellent (CAR is less than 5.0%) when the free S concentration calculated based on the component analysis values of the sample taken in the tundish is 6 ppm by mass or less.
[0037] Based on the above results, in the method of evaluating the hydrogen-induced cracking resistance of steel material of the present invention, a steel material is evaluated as having excellent hydrogen-induced cracking resistance when the segregation evaluation result of the slab is graded B and the free S concentration is 20 ppm by mass or less, or when the segregation evaluation result of the slab is graded A and the free S concentration is 6 ppm by mass or less.
[0038] When the segregation evaluation result of the slab is the above-mentioned evaluation A, the upper limit of the total length of the segregation grains on the segregation line and the upper limit of the maximum length of the segregation grains are not particularly set, but if the total length of the segregation grains of 1.0 mm or more on the segregation line is 75% or less of the survey length and the maximum length of the segregation grains is 8.0 mm or less, excellent HIC properties can be reliably obtained when the free S concentration is 6 mass ppm or less. Furthermore, when the segregation evaluation result of the slab is the above-mentioned evaluation B, there is a mutual correlation between a shortened total length of the segregation grains on the segregation line and a shortened maximum length of the segregation grains, so that when the total length of the segregation grains of 1.0 mm or more on the segregation line is less than 45% of the survey length, there is no need to limit the upper limit of the maximum length of the segregation grains, and similarly, when the maximum length of the segregation grains is less than 3.0 mm, there is no need to limit the upper limit of the ratio of the total length of the segregation grains of 1.0 mm or more on the segregation line to the survey length.
[0039] In other words, in the method of evaluating the hydrogen-induced cracking resistance of a steel material of the present invention, if the segregation evaluation result of the slab is grade B and the free S concentration is more than 6 ppm by mass and not more than 20 ppm by mass, or if the free S concentration is 6 ppm by mass or less regardless of the segregation evaluation result of the slab, the steel material may be evaluated as having excellent hydrogen-induced cracking resistance. EXAMPLES
[0040] Next, an example using the determination method of the present invention will be described. The molten iron tapped from the blast furnace was desulfurized by hot metal pretreatment, dephosphorized and decarbonized in a converter-type refining vessel, and then poured into a ladle. The amount of molten steel was 420 tons. The molten steel in the ladle was transported to an RH vacuum degassing device and refluxed. As sour-resistant steel, the molten steel was desulfurized during the reflux treatment, and Ca was added to the molten steel. The main components, in mass ratio, were C: 0.04 to 0.10%, Mn: 1.0 to 1.5%, P: 100 ppm or less, S: 30 ppm or less, O: 30 ppm or less, and Ca: 50 ppm or less. After treatment in the RH vacuum degassing device, a cast piece was produced by a continuous casting machine. A molten steel sample was taken from the tundish during continuous casting.
[0041] A cross section perpendicular to the longitudinal direction (casting direction) of the slab was cut out so that the C-section could be evaluated from the produced slab. From the cut slab, a sample was further cut out at a position of 1 / 2 the thickness and 1 / 4 the width, polished, and the central segregation part was measured with an EPMA. The investigation was carried out in an area of 25 mm x 25 mm including the central segregation part, and the Mn mapping image obtained was compared with the Mn Seg A portion where / Mn=1.3 or more was extracted as a segregation portion, and a lump of the segregation portion was taken as a segregation grain. A straight line of the investigation length (25 mm) was drawn in the width direction of the slab so as to overlap the segregation grain most in the central segregation zone, and was taken as a segregation line. The length of the segregation grains present on the segregation line (the length of the portion where the segregation grain and the segregation line overlap) was evaluated. Then, the ratio of the total length of the segregation grains (target segregation grains) having a length of 1.0 mm or more to the investigation length (length ratio of segregation grains (target segregation grains) having a length of 1 mm or more) was calculated and shown in the "Segregation grain length ratio" column in Table 1. In addition, the maximum length of the target segregation grains is shown in the "Maximum segregation grain size" column in Table 1. Furthermore, the generation state of inclusions containing MnS was investigated as necessary.
[0042] The steel types used in the examples were CaO The value of E CaO = 40.0 mol % was obtained.
[0043] The composition of the molten steel sample taken from the tundish and the E CaO The results of the investigation of the free S and the central segregation zone of the slab, which were obtained based on the above formulas (1) to (3) based on the values of , are shown in Table 1. Based on the results of the investigation of the segregation zone, the segregation part was evaluated as A under the condition that the ratio of the total length of segregation grains having a length of 1 mm or more to the investigation length (length ratio of segregation grains) among the segregation grains (target segregation grains) present on the segregation line of the investigation length was 45% or more and the maximum length (maximum segregation grain size) of the target segregation grains was 3.0 mm or more, and the rest were evaluated as B, and these are shown in the "Evaluation of segregation part" column in Table 1.
[0044] The results of determining hydrogen induced cracking resistance using the method of the present invention from the evaluation results of free S and segregated areas are shown in the "Results of determination by the present invention" column of Table 1.
[0045] Furthermore, the investigated slabs were rolled into steel plates and then subjected to HIC tests to determine the CAR (%), and the results are shown in the "CAR" column of Table 1. The CAR evaluation method was as described above. Conditions where the CAR was less than 0.5% were evaluated as being particularly excellent in hydrogen-induced cracking resistance, with ◎; conditions where the CAR was between 0.5% and less than 5.0% were evaluated as being excellent in hydrogen-induced cracking resistance, with ○; and conditions where the CAR was 5.0% or more were evaluated as being poor in hydrogen-induced cracking resistance, with ×. These results are shown in the "HIC evaluation" column of Table 1.
[0046] [Table 1]
[0047] In Examples 1 to 11, the total length of the segregated grains having a length of 1 mm or more was less than 45% of the investigated length and / or the maximum length of the segregated grains was less than 3.0 mm, i.e., the segregated portion was rated B and the free S was 20 mass ppm or less. The HIC characteristics were determined to be good by the evaluation method of the present invention, and the CAR value investigated on the steel sheet was also good at less than 5.0%.
[0048] In Examples 12 and 13, the segregation portion was rated B, the free S content was more than 20 ppm by mass, the HIC characteristics were determined to be poor by the evaluation method of the present invention, and the CAR value investigated on the steel sheet was also low at 5.0% or more.
[0049] In Examples 14 to 22, the total length of the segregated grains of 1 mm or more was 45% or more of the measured length, and the maximum length of the segregated grains was 3.0 mm or more, i.e., the segregated portion was rated A and the free S was 6 ppm by mass or less. The HIC characteristics were determined to be good by the evaluation method of the present invention, and the CAR value measured on the steel sheet was also good at less than 5.0%.
[0050] In Examples 23 to 28, the segregation evaluation results were rated as A, the free S content was more than 6 ppm by mass, the HIC characteristics were determined to be poor by the evaluation method of the present invention, and the CAR value investigated on the steel sheet was also low at 5.0% or more.
[0051] As described above, the results of determining hydrogen-induced cracking resistance using the free S obtained from the molten steel sample collected in the tundish using the method of the present invention and the evaluation results of the segregated grains in the central segregation zone of the slab matched the results of the CAR investigated on the steel plate after rolling. This result supports the idea of the present invention that MnS is the starting point of HIC, the size of the segregated grains affects the size of the cracks in the segregated grains, and the dispersion state of the segregated grains affects the propagation of the cracks, and it can be seen that the present invention is useful as a method for evaluating the hydrogen-induced cracking resistance of steel materials.
[0052] In addition, a technique using the results of an investigation of segregation parts to evaluate the hydrogen-induced cracking resistance of steel has been disclosed as a conventional technique, but by only evaluating the segregation parts, all of Examples 14 to 28 in which the evaluation of the segregation parts was judged to be A, including the condition where the CAR value was 5.0% or more, would be judged to have poor HIC properties, and measures such as lowering the grade of the steel would be necessary. In the present invention, by combining with free S at the molten steel stage, Examples 12 and 13 were excluded under the condition where the evaluation of the segregation parts was judged to be B, and Examples 14 to 22 in which the hydrogen-induced cracking resistance of the steel was good under the condition where the evaluation of the segregation parts was judged to be A could be extracted, which shows that this technique is superior to the conventional techniques.
Claims
1. A method for evaluating hydrogen-induced cracking resistance of a steel material, the method comprising the steps of: evaluating the hydrogen-induced cracking resistance of a steel material based on a free S concentration calculated based on a component analysis value of a molten steel sample taken in a tundish and an evaluation result of segregation grains in a central segregation zone appearing in a cross section perpendicular to the longitudinal direction of a cast slab, the method comprising the steps of: The free S concentration is calculated by determining E CaO (the ratio (mol %) of CaO to all oxides in the molten steel) for each type in advance, and calculating the free S concentration based on the component analysis values of the sample according to the following formulas (1) to (3): The segregated grains are evaluated by an etch print method or an EPMA method. In the etch printing method, a grayscale image of an etch print onto which a region including a segregated portion is transferred is photographed, and the image converted to a grayscale is binarized. The binarized thickened portion is regarded as a segregated portion, and one lump of the segregated portion is regarded as a segregated grain. In the method using the EPMA, a mapping image of Mn is obtained in a test piece including a segregated portion, and with respect to the relationship between the Mn concentration of the base material: Mn and the Mn concentration of the EPMA measurement portion: Mn Seg , a portion where Mn Seg / Mn = 1.3 or more is defined as a segregated portion, and a lump of the segregated portion is defined as a segregated grain, In both the etch print method and the method using EPMA, a straight line of a predetermined investigation length is drawn in the width direction of the slab so as to overlap most closely with the segregated grains on the image of the central segregation zone, and the length of the segregated grains present on the straight line (segregation line) (the length of the portion where the segregated grains and the segregation line overlap) is evaluated. A method for evaluating hydrogen-induced cracking resistance of a steel material, comprising: Ca CaO = (T.O / 16)・40.078・(E CaO / 100) ... (1) S CaS = (Ca-CaCaO)・32 / 40.078...(2) Free S = S - S CaS ... (3) T.O is the total oxygen concentration analysis value (ppm by mass), Ca is the Ca concentration analysis value (ppm by mass), and S is the S concentration analysis value (ppm by mass).
2. 2. The method for evaluating hydrogen-induced cracking resistance of a steel material according to claim 1, characterized in that the steel material is evaluated as having excellent hydrogen-induced cracking resistance when, among segregated grains on a straight line (segregation line) of a predetermined investigation length drawn in the width direction of the slab so as to overlap most with the segregated grains in the central segregation zone, the total length of segregated grains (target segregated grains) having a length (the length of a portion where the segregated grains and the segregation line overlap) of 1.0 mm or more is less than 45% of the investigation length and / or the maximum length of the target segregated grains is less than 3.0 mm, and the free S concentration is 20 ppm by mass or less.
3. 2. The method for evaluating hydrogen-induced cracking resistance of a steel material according to claim 1, characterized in that the steel material is evaluated as having excellent hydrogen-induced cracking resistance when, among segregated grains on a straight line (segregation line) of a predetermined investigation length drawn in the width direction of the slab so as to overlap most with the segregated grains in the central segregation zone, the total length of segregated grains (target segregated grains) having a length (the length of a portion where the segregated grains and the segregation line overlap) of 1.0 mm or more is 45% or more of the investigation length, the maximum length of the target segregated grains is 3.0 mm or more, and the free S concentration is 6 ppm by mass or less.
Citation Information
Patent Citations
Compressor drive power source for air conditioner
JP1984010195A
Generator of record timing pulse
JP1985032166A
Estimation method of HIC sensitivity of steel material and manufacturing method of high strength thick steel plate for line pipe superior in anti HIC performance using the same
JP2014077642A
Destination change method by qualitative determination of sour-resistant steel slab
JP2014172074A
Method of estimating hydrogen-induced cracking resistance of calcium-added steel
JP2015059880A